2020
DOI: 10.3390/vaccines8010139
|View full text |Cite
|
Sign up to set email alerts
|

Recent Progress on the Versatility of Virus-Like Particles

Abstract: Virus-like particles (VLPs) are multimeric nanostructures composed of one or more structural proteins of a virus in the absence of genetic material. Having similar morphology to natural viruses but lacking any pathogenicity or infectivity, VLPs have gradually become a safe substitute for inactivated or attenuated vaccines. VLPs can achieve tissue-specific targeting and complete and effective cell penetration. With highly ordered epitope repeats, VLPs have excellent immunogenicity and can induce strong cellular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
125
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(126 citation statements)
references
References 110 publications
0
125
0
1
Order By: Relevance
“…The highly repetitive antigenic surface of VLP vaccines also help induce stronger antibody response by efficiently cross-linking B-cell surface receptors. Up to now, VLP vaccines have been commercialized for the protection against human papillomavirus (Cervarix ™ and Gardasil ® ) and hepatitis B virus (Engerix ® and Recombivax HB ® )[52].Few SARS-CoV and MERS-CoV VLP vaccines have been reported so far. For SARS-CoV, Lokugamage et al have demonstrated that chimeric VLPs composed of SARS-CoV S protein and mouse hepatitis virus E, M and N proteins can induce neutralizing antibody responses and reduce SARS-CoV virus titer in mice lung after viral challenge…”
mentioning
confidence: 99%
“…The highly repetitive antigenic surface of VLP vaccines also help induce stronger antibody response by efficiently cross-linking B-cell surface receptors. Up to now, VLP vaccines have been commercialized for the protection against human papillomavirus (Cervarix ™ and Gardasil ® ) and hepatitis B virus (Engerix ® and Recombivax HB ® )[52].Few SARS-CoV and MERS-CoV VLP vaccines have been reported so far. For SARS-CoV, Lokugamage et al have demonstrated that chimeric VLPs composed of SARS-CoV S protein and mouse hepatitis virus E, M and N proteins can induce neutralizing antibody responses and reduce SARS-CoV virus titer in mice lung after viral challenge…”
mentioning
confidence: 99%
“…Such epitopes, once improved in their antigenic properties, can be included in specific delivery carriers to protect them from degradation (Allahyari and Mohit, 2016): they include VLPs, liposomes, polymeric micro-/nano-particles and dendrimeric systems that are schematically described in Figure 2 (Neek et al, 2019;Singh et al, 2007). In VLPs, (Figure 2A), the antigen can be immobilized on the surface through biochemical tools or covalent links (Sapsford et al, 2013;Qian et al, 2020;Koho et al, 2015;Syomin and Ilyin, 2019). The advantages of VLPs include similar size and antigenicity of the corresponding viruses and lack of viral genome and, as consequence, of danger.…”
Section: Peptide-based Vaccines In Diseasesmentioning
confidence: 99%
“…By contrast, the structure of VLPs are similar to the conformation of wild type viruses which can activate adaptive immunity ( 134 ). VLPs can be modified by chemical or genetic fusion technologies to express chimeras or targeted delivery of small molecule drugs and nucleic acids as a result of the improvement of bioavailability of the delivered substance ( 135 ). Thus, VLPs can restore immune response, cross-present and induce CTL responses.…”
Section: Possibilities Of Nanomaterials In Clinical Tumor Immunotheramentioning
confidence: 99%